Therapeutic Effect of Modulating TREM-1 via Anti-inflammation and Autophagy in Parkinson’s Disease - Feng, Chien-Wei; Chen, Nan-Fu; Sung, Chun-Sung; Kuo, Hsiao-Mei; Yang, San-Nan; Chen, Chien-Liang; Hung, Han-Chun; Chen, Bing-Hung; Wen, Zhi-Hong; Chen, Wu-Fu (Frontiers in Neuroscience, 2019)
Parkinson’s disease (PD) is one of the most common age-related neurodegenerative diseases, and neuroinflammation has been identified as one of its key pathological characteristics. Triggering receptors expressed on myeloid cells-1 (TREM-1) amplifies the inflammatory response and plays a role in sepsis and cancer. Recent studies have demonstrated that the attenuation of TREM-1 activity produces cytoprotective and anti-inflammatory effects in macrophages. However, no study has examined the role of TREM-1 in neurodegeneration. We showed that LP17, a synthetic peptide blocker of TREM-1, significantly inhibited the lipopolysaccharide (LPS)-induced upregulation of proinflammatory cascades of inducible nitric oxide synthase (iNOS), cyclooxygenase-2, and nuclear factor-B. Moreover, LP17 enhanced the LPS-induced upregulation of autophagy-related proteins such as light chain-3 and histone deacetylase-6. We also knocked down TREM-1 expression in a BV2 cell model to further confirm the role of TREM-1. LP17 inhibited 6-hydroxydopamine-induced locomotor deficit and iNOS messenger RNA expression in zebrafish. We also observed therapeutic effects of LP17 administration in 6-OHDA-induced PD syndrome using a rat model. These data suggest that the attenuation of TREM-1 could ameliorate neuroinflammatory responses in PD and that this neuroprotective effect might occur via the activation of autophagy and anti-inflammatory pathways.